The Parylene C as a Flexible Substrate and Passivation Layer: A Promising Candidate for a Piezoelectric, Piezoresistive, and Capacitive Pressure Sensor in Low-Pressure Range - Kurnaz, Sedat; Öztürk, Özgür; Yılmaz, Nurdane; Çiçek, Osman (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Parylene C is widely used as a passivation layer due to its excellent chemical inertness, electrical insulation, biocompatibility, and flexibility. But, it is a potential piezoelectric material that can be used as a flexible pressure sensor. Herein, the parylene C is synthesized via the chemical vapor deposition method. The flexible piezoelectric, piezoresistive, and capacitive pressure sensors based on parylene C are fabricated. The flexible piezoelectric pressure sensor is used for the first time. The sensing performance of these sensors is comparatively investigated, showing high sensitivities of 140 mV center dot kPa(-1), 0.046 kPa(-1), and 0.080 kPa(-1) in the low-pressure range (<4 kPa), respectively. Furthermore, the response times (0.40, 0.37, and 0.48 s) and the relaxation times (0.21, 0.37, and 0.62 s) are achieved. This work demonstrates that parylene C, which is often used as a passivation layer, can also be used as a flexible piezoresistive and capacitive pressure sensor. It could also be a potential candidate for wearable healthcare monitoring, human-machine interfaces, and soft robotics in the low-pressure range.
Keywords: 7. Clean energy